Amino-terminal sequence of the Tn3 transposase protein. - Ditto, M D (1982)
The amino-terminal sequence of the Tn3 transposase protein was determined to be Pro-Val-Asp-Phe-Leu-Thr-Thr-Glu-Gln-Val-Glu-Ser.... This was determined both from an active transposase protein purified from a transposase overproducing mutant strain and from a hybrid transposase-beta-galactosidase fusion protein. The amino acid sequence corresponded to the DNA sequence of the transposase gene beginning at an ATG initiation codon, as previously predicted from the analysis of transposase-beta-galactosidase gene fusions.